Population Pharmacokinetics and Pharmacodynamics of Isoniazid and its Metabolite Acetylisoniazid in Chinese Population - Chen, Bing; Shi, Hao-Qiang; Feng, Meihua Rose; Wang, Xi-Han; Cao, Xiao-Mei; Cai, Wei-Min (Frontiers in Pharmacology, 2022)
Objective: We aimed to establish a population pharmacokinetic (PPK) model for isoniazid (INH) and its major metabolite Acetylisoniazid (AcINH) in healthy Chinese subjects and tuberculosis patients and assess the role of NAT2 genotype on the transformation of INH to AcINH. We also aimed to estimate the INH exposure that achieved 90% effective concentration (EC90) efficiency for patients with various NAT2 genotypes and dosing regimen. Method: A total of 45 healthy subjects and 157 tuberculosis patients were recruited. For healthy subjects, blood samples were collected 0-14 h after administration of 300 mg or 320 mg of the oral dose of INH; for tuberculosis patients received at least 7 days therapy with INH, blood samples were collected 2 and/or 6 h post administration. The plasma concentration of INH and AcINH was determined by reverse-phase HPLC method. NAT2 genotypes were determined by allele specific amplification. The integrated PPK model of INH and AcINH was established through nonlinear mixed-effect modeling (NONMEM) method. The effect of NAT2 genotype and other covariates on INH and AcINH disposition was evaluated. Monte Carlo simulation was performed separately for estimating EC90 of INH in patients with various NAT2 genotypes. Results: The estimated absorption rate constant Ka, oral clearance (CL/F), and apparent volume of distribution (V2/F) for INH were 3.94±0.44 1/h, 18.2 ± 2.45 L/h, and 56.8 ± 5.53 L, respectively. The constant of clearance (K30) and the volume of distribution (V3/F) of AcINH were 0.33 ± 0.11 1/h and 25.7 ± 1.30 L, respectively. The fraction of AcINH formation (FM) was 0. 81± 0.076. NAT2 genotypes had different effects on the CL/F and FM. In subjects with only one copy of NAT2 *5, *6, and *7 alleles, the CL/F values were approximately 46.3%, 54.9%, and 74.8% of *4/*4 subjects, respectively. The FM values were approximately 48.7%, 63.8%, and 86.9% of *4/*4 subjects, respectively. The probability of target attainment of EC90 of INH in patients with various NAT2 genotypes was different. Conclusion: The integrated parent-metabolite PPK model accurately characterized the disposition of INH and AcINH in Chinese population, which may be useful in the individualized therapy of INH.